Exploring auditory morphodynamics: Audiovisual associations in sound-based music - Riccardo Wanke; Alessandro Ansani; Nicola Di Stefano; Charles Spence (i-Perception)
This article explores audiovisual associations within the context of contemporary and experimental music practices, particularly focusing on sound-based music. While extensive studies exist on crossmodality in relation to traditional music genres (such as classical instrumental music), the perceptual potential of sound-based music remains an underexplored field of psychological research. In an online procedure, 152 participants were exposed to six musical excerpts from spectralism and electronic-glitch music and were asked to rate the extent to which each audio matched with six ad hoc generated black and white abstract images. Statistical analysis revealed that ratings were highly consistent across participants, indicating that they may rely on a shared set of implicit perceptual criteria rooted in Gestalt and morphodynamic features common to both auditory and visual stimuli. In particular, smoothness, continuity, numericity, symmetry, and spectrotemporal dimensions emerged as the primary factors influencing the association ratings. We discuss the implication of these findings both for crossmodal research and musicology, and suggest some directions for future research in audiovisual associations using sound-based music.